1984
DOI: 10.1111/j.1476-5381.1984.tb10796.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase inhibitors antagonize indirectly evoked contractions of the guinea‐pig isolated ileum by inhibiting acetylcholine release

Abstract: 1The effects of indomethacin, sodium meclofenamate and ketoprofen on the contractile responses of the guinea-pig isolated ileum to directly and indirectly evoked stimuli were investigated. The effects of the cyclo-oxygenase inhibitors on acetylcholine (ACh) release from plexus containing longitudinal muscle strips were also studied. 2 The cyclo-oxygenase inhibitors reduced contractile responses to transmural stimulation (TMS) and nicotine at concentrations which had no effect on ACh-induced contractions.3 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The animals were killed by CO 2 and bled. Guinea-pig ileum was prepared as described previously (Okpako and Taiwo, 1984). Pieces of ileum, 2-3 cm long were set up in a 10 mL organ bath contaiing Tyrode solution with 5% CO 2 in 95% oxygen: the solution was maintained at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were killed by CO 2 and bled. Guinea-pig ileum was prepared as described previously (Okpako and Taiwo, 1984). Pieces of ileum, 2-3 cm long were set up in a 10 mL organ bath contaiing Tyrode solution with 5% CO 2 in 95% oxygen: the solution was maintained at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were sacrificed by cervical dislocation. Guinea-pig ileum was prepared as previously described (Okpako and Taiwo, 1984). Pieces of ileum, 2-3 cm long, were set up in 10 ml organ bath containing Tyrode solution with 5% CO 2 in 95% oxygen; the solution was maintained at 37°C.…”
Section: Transmurally Stimulated Guinea-pig Ileum Testmentioning
confidence: 99%
“…Contradictory results have been obtained in studies with nicotine, which has been shown to activate the soma of myenteric neurones (Yagasaki et al, 1984;Wood, 1987). Ind inhibited both the release of ACh from the myenteric plexus and the response of the enteric inhibitory nerves in the taenia coli to nicotine (Okpako & Taiwo, 1984;Yagasaki et al, 1984;Iselin et al, 1988). Such inhibition was overcome by prostaglandin E2 (PGE2).…”
Section: Introductionmentioning
confidence: 99%